Über die Synärese kolloidaler Strukturen am Beispiel von Siliciumdioxid - Wilhelm, Sebastian Maximilian (KIT Scientific Publishing, 2017)
Silica is a naturally occuring solid substance with either a crystalline or amorphous structure. Industrially produced amorphous silica has a wide field of application. During the production process of amorphous silica, syneresis of the solid structures created occurs. In this work, the influences of the process parameters on syneresis are determined experimentally and a physically based model is proposed to describe syneresis.